(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a typological comparison of tense and aspect systems in English, a Germanic analytic language, and Uzbek, a Turkic agglutinative language. Drawing on established frameworks from Comrie (1976) and Bybee et al. (1994), we examine how these categories are morphologically realized, semantically interpreted, and pragmatically employed. English relies on periphrastic constructions for aspectual distinctions (e.g., progressive and perfect), while Uzbek integrates tense and aspect through suffixes, emphasizing imperfective and perfective oppositions. Key differences include English’s binary tense system (past/non-past) versus Uzbek’s multifaceted past tenses and evidential nuances. Similarities emerge in expressing ongoing actions and resultative states. The analysis highlights implications for second language acquisition and translation, supported by parallel corpus examples. Findings underscore the role of typology in cross-linguistic transfer, with pedagogical recommendations for Uzbek-English learners.